Kali dodecanesicum (Chenopodiaceae, Salsoloideae) a new species from Greece - Brullo, Cristian; Brullo, Salvatore; Ilardi, Vincenzo; Galdo, Gianpietro Giusso Del (Phytotaxa, 2015)
Kali dodecanesicum, a new species from some islands (i.e. Rhodes, Kos and Nisyros) of the Dodecanese in the south-eastern Aegean (Greece), is described and illustrated. According to recent literature, Kali is treated as a distinct genus from the polyphyletic Salsola s.l., which includes several annual species. The new species is morphologically well separated from the other Kali taxa mainly for the shape of the fruiting perianth, showing closer relationships with Kali ponticum. Its ecological requirements, distribution, and conservation status are also examined, together with an analytic key of the Kali species occurring in the Mediterranean area.